Efficacy of Antibiotic Prophlaxis in Preventing Surgical Site Infections: A Review of Current Practices and Emerging Alternatives in General and Plastic Surgery - Asghar Ali, Javed Iqbal Khan, Hafiz Waqas Ahmed, Tanveer Sadiq Ch, Mufassar Nishat, Sumaira Otho, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Effective preventive measures are necessary to reduce the incidence of surgical site infections (SSIs), which continue to be a leading cause of postoperative morbidity. Objective: This study aimed to evaluate the efficacy of antibiotic prophylaxis in preventing SSIs in general and plastic surgery, compare different antibiotic regimens, and analyze factors influencing infection rates. Methodology: A prospective observational study was conducted from at the department of Surgery, Mardan Medical Complex, Mardan from January 2022 to December 2022. There were 116 patients in all having either general or plastic surgery. Based on surgical indications, cefazolin, cefuroxime, or clindamycin-gentamicin were used in antibiotic prophylaxis in accordance with FDA recommendations. To evaluate the incidence of SSI, patients were monitored for 30 days after surgery. SPSS version 25 was used to gather and analyze data on patient demographics, comorbidities, wound categorization, surgery specifics, and preventative measures. Chi-square tests were used for categorical variables. Results: General surgery had a greater infection rate than plastic surgery, with an overall SSI incidence of 14.66%. With the lowest infection incidence, cefazolin was the most effective antibiotic; SSI rates were greater for cefuroxime and clindamycin-gentamicin. While the difference in SSI rates between general and plastic surgery was not statistically significant, wound classification and the presence of drains were strongly linked with infection risk (p < 0.05). Conclusion: The most effective drug cefazolin proves to significantly reduce the possibility of surgical site infection according to research. Perioperative infection control methods must be optimized because of this requirement. Keywords: Surgical site infection, antibiotic prophylaxis, general surgery, plastic surgery, cefazolin, infection control